2016
DOI: 10.1002/2015jg003231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organic matter source and quality on living benthic foraminiferal distribution on a river‐dominated continental margin: A study of the Portuguese margin

Abstract: Living (rose Bengal stained) benthic foraminifera were investigated on surface sediments from 23 stations from the river-dominated northwestern Portuguese margin. Samples were collected in March 2011, following the period of the maximum rainfall over the Iberian Peninsula, between 20 and 2000 m water depth along five cross-margin transects. Four of them are located off the Douro, Mondego, Tagus, and Sado Rivers and one off the Estremadura coast. The major objectives of this study are (1) to assess the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 111 publications
1
19
0
Order By: Relevance
“…Microhabitat controls faunal distribution (density and diversity) mainly through its physical and chemical properties like grain size, oxygen depletion, and source, quantity, and quality of the organic matter stocked in the sediment (e.g., Jorissen et al, 1995;Schönfeld, 2002;Dessandier et al, 2016). The impact of organic content on benthic foraminiferal density and diversity is unclear at the locations of this study.…”
Section: Foraminiferal Response To Gas Charged Sedimentsmentioning
confidence: 86%
“…Microhabitat controls faunal distribution (density and diversity) mainly through its physical and chemical properties like grain size, oxygen depletion, and source, quantity, and quality of the organic matter stocked in the sediment (e.g., Jorissen et al, 1995;Schönfeld, 2002;Dessandier et al, 2016). The impact of organic content on benthic foraminiferal density and diversity is unclear at the locations of this study.…”
Section: Foraminiferal Response To Gas Charged Sedimentsmentioning
confidence: 86%
“…Bouchet (2007) suggests that the sedimentary detrital organic matter represents the main food resource for this species. Dessandier et al (2016) studied the distribution of E. scaber along the Portuguese coast, highlighting its preference for environments characterized by high-quality of the organic matter (e.g., high chlorophyll-a to phaeopigment ratio and available amino acids). Murray (2013) reported that E. scaber is sensitive to salinity not exceeding 24 psu and oxygen depletion (<0.5 ml/L), and that it is tolerant to fluctuations in temperature and heavy metal pollution.…”
Section: Living Foraminifera Assemblages and Their Significancementioning
confidence: 99%
“…This is particularly true for river-dominated shelves where living benthic foraminifera have been identified to respond to river inputs (e.g., Mendes et al, 2004;Mojtahid et al, 2009;Goineau et al, 2011). Dessandier et al (2016Dessandier et al ( , 2018 have shown through studies on living and dead faunas that some species could be used as bio-indicators of river discharge and upwelling intensity in the Portuguese Margin. During the last millennia, these environmental conditions were influenced by rapid climatic changes (Abrantes et al, 2005.…”
Section: Introductionmentioning
confidence: 99%